2018
DOI: 10.1002/hbm.23956
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery training: Kinesthetic imagery strategy and inferior parietal fMRI activation

Abstract: Motor imagery (MI) is the mental simulation of action frequently used by professionals in different fields. However, with respect to performance, well-controlled functional imaging studies on MI training are sparse. We investigated changes in fMRI representation going along with performance changes of a finger sequence (error and velocity) after MI training in 48 healthy young volunteers. Before training, we tested the vividness of kinesthetic and visual imagery. During tests, participants were instructed to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 52 publications
0
25
2
Order By: Relevance
“…This is different from the typical silent counting task used in evoking P300 responses, which largely depends on the sensory perception and anticipation of the bottom-up physical features of the stimulus. The 0.8 Hz rhythmic mental operation activated the region of the left IOG, which is reported to be associated with verbal representation (Saito et al, 2012) and memory maintenance in numeral processing (Daitch et al, 2016), and the region of the right IPL, which is associated with auditory working memory (Paulesu et al, 1993) and has also been proposed to be activated in imagined singing and imagined movement (Kleber et al, 2007; Lebon et al, 2018). In addition, our study shows that the ventral PrG and PoG are also activated during the construction of speech imagery, which is consistent with previous findings that stronger activation of the sensorimotor cortex induced by articulatory imagery than hearing imagery (Tian et al, 2016) and the direct neural signal from the sensorimotor cortex contributed to the decoding of imagined speech and silent reading (Martin et al, 2014; Martin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This is different from the typical silent counting task used in evoking P300 responses, which largely depends on the sensory perception and anticipation of the bottom-up physical features of the stimulus. The 0.8 Hz rhythmic mental operation activated the region of the left IOG, which is reported to be associated with verbal representation (Saito et al, 2012) and memory maintenance in numeral processing (Daitch et al, 2016), and the region of the right IPL, which is associated with auditory working memory (Paulesu et al, 1993) and has also been proposed to be activated in imagined singing and imagined movement (Kleber et al, 2007; Lebon et al, 2018). In addition, our study shows that the ventral PrG and PoG are also activated during the construction of speech imagery, which is consistent with previous findings that stronger activation of the sensorimotor cortex induced by articulatory imagery than hearing imagery (Tian et al, 2016) and the direct neural signal from the sensorimotor cortex contributed to the decoding of imagined speech and silent reading (Martin et al, 2014; Martin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…2 Other more recent studies, found that while physical practice is associated with increased activation in premotor regions and cerebellum (e.g., SMA and cerebellum in Nyberg et al, 2006; ventral premotor cortex, BA 6/44 in Olsson et al, 2008b) or decreased activation of the posterior parietal cortex (Olsson et al, 2008a), M.I. training of motor sequences is associated with a specific increased activity in the parietal cortex (Lebon et al, 2018) or in the visual occipital cortex (BA 18 in Nyberg et al, 2006; fusiform gyrus, BA 19, in Olsson et al, 2008b). Increased activity in the fusiform gyrus was also found by Zhang and coworkers in both motor execution and motor imagery tasks after a 2-week of motor imagery training (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…To better understand the dysfunction of the T2DM brain, it is essential to consider how the brain regions work together rather than studying them in isolation. On the one hand, high visual cortex recruitment predicted poor motor execution, which was represented by the strong activation of the inferior parietal cortex (Lebon et al, 2018). The caudate nucleus subserves not only the complex regulation of mood but also the executive function (Yang et al, 2015;Huang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%